2020
DOI: 10.3389/fpsyg.2020.01361
|View full text |Cite
|
Sign up to set email alerts
|

The Testing of a Four-Dimensional Model of Athlete Leadership and Its Relation to Leadership Effectiveness

Abstract: Athlete leadership researchers have typically investigated three dimensions of athlete leadership behaviors, which include the meta-categories of task-, social-, and externaloriented leadership. More recently, motivational leadership was added as a fourth dimension. Researchers in organizational leadership have advanced another dimension, referred to as change-oriented leadership (Yukl, 2012). Therefore, in the present study, we tested a four-dimensional model that includes the dimensions of task-, social-, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…Precisely, our study extends the established view of change-oriented leadership’s effect on organisational performance, indicating that change-oriented leadership does not only affect organisational performance but also organisational innovation. Furthermore, this work adds empirical evidence to the extant association between on change-oriented leadership and organisational performance (Andersen, 2010; Bergsten et al , 2021; Elkomy et al , 2020; Fan et al , 2020; Ghasemy et al , 2020; Katz et al , 2009; Maechel et al , 2020; Maladzhi, 2015; Øygarden et al , 2020) by proposing and confirming the mediation role of organisational innovation on the relationship between change-oriented leadership and organisational performance. Although prior studies have examined the mediating role of organisational innovation on the effect of various leadership styles on organisational performance (Ebrahimi et al , 2016; Sethibe and Steyn, 2015; Zehir et al , 2012), such studies did examine the mediating effect of organisational innovation along with the path from change-oriented leadership to organisational performance.…”
Section: Theoretical Contributionssupporting
confidence: 53%
“…Precisely, our study extends the established view of change-oriented leadership’s effect on organisational performance, indicating that change-oriented leadership does not only affect organisational performance but also organisational innovation. Furthermore, this work adds empirical evidence to the extant association between on change-oriented leadership and organisational performance (Andersen, 2010; Bergsten et al , 2021; Elkomy et al , 2020; Fan et al , 2020; Ghasemy et al , 2020; Katz et al , 2009; Maechel et al , 2020; Maladzhi, 2015; Øygarden et al , 2020) by proposing and confirming the mediation role of organisational innovation on the relationship between change-oriented leadership and organisational performance. Although prior studies have examined the mediating role of organisational innovation on the effect of various leadership styles on organisational performance (Ebrahimi et al , 2016; Sethibe and Steyn, 2015; Zehir et al , 2012), such studies did examine the mediating effect of organisational innovation along with the path from change-oriented leadership to organisational performance.…”
Section: Theoretical Contributionssupporting
confidence: 53%
“…The authors delivered four separate workshops over the course of the season to three teams (while three other teams served as a control group). These four workshops were designed using the four athlete leadership meta-categories advanced by Maechel et al (2020) that contained social, task, change and external-oriented forms of leadership. Using a mixed-methods approach, the quantitative data showed that all four meta-categories were significantly higher for the three teams in the intervention condition compared to the control condition.…”
Section: Leadership Developmentmentioning
confidence: 99%
“…The study conducted by Fransen et al (2014) emphasised the relevance of this leadership classification by demonstrating that an effective fulfilment of the four leadership roles by members of the team resulted in higher team confidence, stronger team identification and better team performance outcomes (e.g., ranking). Expanding upon the work of Fransen et al (2014) , Maechel et al (2020) suggested an additional change-oriented leadership role, focused on promoting change and innovation and encouraging team learning.…”
Section: Introductionmentioning
confidence: 99%